Penanganan Banjir Sub-DAS Posindo Kota Balikpapan dengan Optimalisasi Penyediaan Infrastruktur Hijau - Achmad Ghozali; Rossana Margaret Kadar Yanti; Ajeng Nugrahaning Dewanti (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2022)
The Posindo sub-basin, emptying into the Ampal river, is experiencing floods, yet the city government has regularly normalized and cleaned the river. Therefore, this problem cannot be handled conventionally and generically. The research was conducted to formulate optimal flood management scenarios through a green infrastructure approach as an alternative for sustainable flood management. Two analytical methods were used to overcome the research question: the Gumbel Type I distribution to calculate rainfall return periods and HEC-HMS and HEC-RAS modeling software to simulate hydrological and hydraulic conditions. Result analysis showed an overflow discharge above the embankment along the Posindo sub-basin secondary channel by 0.38 – 1.64 m3/s. Alternative’s simulation shows that providing green open space (GOS) is crucial for maintaining water balance in the study area. The combined management scenario by maintaining a minimum GOS of 10%, storage ponds establishment, and increasing the drainage capacity adequate to reduce the overflow height.